Patterns and Reasons for Extracted Primary Teeth in Children Attending a Pediatric Dental Teaching Clinic - Hussein, Alaa; Venkiteswaran, Annapurny; Zaki, Mohamad; Zin, Muhamad; Al-Naser, Mohammed (Jordan Medical Journal, 2023)
Introduction: Understanding the patterns and reasons why children’s primary teeth are extracted is crucial to improve oral health outcomes among children. Objective: This retrospective study aimed to determine the patterns and reasons for primary teeth extraction in children attending a dental teaching clinic in Malaysia. Materials and methods: Between 2009 and 2019, dental records were screened by undergraduate students for patients aged under 16 years who had undergone primary tooth extraction. Data were collected on age, gender, indications and year of tooth extraction, as well as type of tooth extracted. Descriptive statistics and bivariate association analysis were performed. A p value ≤ 0.05 was considered statistically significant. Results: 1,785 teeth were extracted. Females had more tooth extractions than males. Tooth extraction was common among the 7–9 years old group (47.2%). The most frequently extracted primary tooth was the first molar (29.1%), whereas the lateral incisor was the least (11.7%). Extraction due to dental caries was the main reason among all age groups (57.5%), followed by shedding time (38.1%). Statistical differences were found between patterns and reasons for tooth extraction and age groups (p< 0.05). However, no significant differences were observed in terms of the age and year of extraction (p> 0.05). Conclusions: First molars were the most frequently extracted teeth. Dental caries and its sequelae remain the foremost cause of dental extraction among this sample of Malaysian children. The development of appropriate oral health education programs on the importance of primary teeth, alongside early dental examination, are recommended to prevent tooth extraction.